Refeeding Syndrome in Surgical Patients. A Clinical Case Analysis - M. A. Nartailakov; I. Z. Salimgareev; V. S. Panteleev; F. R. Nagaev; V. V. Pogаdaev; V. V. Rezyapov; I. I. Ivanov (Креативная хирургия и онкология, 2019)
Introduction. Refeeding syndrome is a condition underpinned by metabolic disorders emerging as a result of the resumption of feeding in patients after a protracted period of starvation. The real figures of the potentially life threatening refeeding syndrome incidence are unknown. This paper aims to demonstrate the clinical picture and methods of resolving of the refeeding syndrome by presenting a clinical case.Materials and methods. The clinical presentation of the refeeding syndrome with pronounced neurological and cardiological symptoms is demonstrated on the example of a female patient with acute pancreatitis of medium severity at the resumption of enteral feeding. A review of available literature on the subject is also presented.Results and discussion. The range of diagnostic considerations was rather broad as the authors had to eliminate acute coronary and neurological disorders. The auxiliary laboratory examination methods helped form the hypothesis of a developing refeeding syndrome and correct the treatment. Parenteral phosphate-containing preparations and enteral feeding with phosphates were administered. The patient was transferred to the neurology department for further treatment. The patient was discharged home on day 53 with total regression of neurological symptoms.Conclusion. Hypophosphataemia — a very low level of phosphorus in blood — is a key clinical marker of the syndrome. However, low blood levels of potassium, calcium, magnesium and vitamin В1 may also play a role. Chronically undernourished patients and those not having any enteral feed for over 10 days are fall in the high risk group. The feeding should be resumed at a low level energy intake. Vitamins should be prescribed at the resumption and continued for at least 10 days. The electrolyte and fluid balance does not have to be corrected prior to the resumption of feeding; it can be done simultaneously with feeding.